Evaluasi Efisiensi Dye Sensitized Solar Cell melalui Penggunaan Hidrogel Elektrolit PEG dan Dye Ekstrak Daun Eceng Gondok - Azra, Muhammad Rizki; Tamrin, Tamrin; Pratama, Filli; Ramadhani, Imes Suci (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Azra, M. R., Tamrin, T., Pratama, F., & Ramadhani, I. S. (2024). Efficiency evaluation of dye sensitized solar cell through the use of PEG electrolyte hydrogel and water hyacinth leaf extract dye. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 426–433). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The research that has been conducted is a study of the effect of the Use of PEG electrolyte hydrogels on the performance of Dye Sensitized Solar Cells with water hyacinth leaf dye extract. This research aimed to study and determine the performance of dye sensitized solar cells using a variety of electrolyte hydrogels based on PEG 4000 and PEG 6000 with concentrations of 5%, 10% and 15% respectively. This study measured the absorbance of water hyacinth leaf dyes using a UV-VIS spectrophotometer and to determine the performance DSSC itself measured using a multimeter which was carried out with a light source of the halogen lamp. The parameters observed in this study dye absorption, current and voltage, power calculation, fill factor, and DSSC efficiency. The results showed that the use of PEG-based electrolyte hydrogels in DSSC can increase the efficiency and stability of DSSC use. The best DSSC performance using water hyacinth dye extract with the use of PEG-based electrolyte hydrogel occurred in DSSC G with 15% PEG 6000. The electrical characters produced on the sample are Isc: 0.0133 mA, Voc: 0.698 mV, Imax: 0.0073 mA, Vmax: 0.534 mV, Pmax: 0.003898 mW, FF: 0.62856, and efficiency of 0.021%.